Electro-remediation of tailings from a multi-metal sulphide mine: comparing removal efficiencies of Pb, Zn, Cu and Cd. Issue 1 (2nd January 2019) - Zhang, Zhaoyu; Ottosen, Lisbeth M.; Wu, Tairan; Jensen, Pernille E.
ABSTRACT: Sulphidic mine tailings characterised by high concentrations of heavy metals (Pb 3532 ± 97 mg/kg, Zn 8450 ± 154 mg/kg, Cu 239 ± 18 mg/kg and Cd 14.1 ± 0.3 mg/kg) and abundant carbonate (17%) were subjected to eight lab-scale electrodialytic remediation (EDR) experiments to investigate the influence of current density, treatment time and particle size on removal efficiency. Pb and Cu removal improved when increasing current density, while Zn and Cd removal did not. In contrast Zn and Cd removal improved by grinding the tailings, while Pb and Cu removal did not. At the highest current density (1.2 mA/cm 2 ), 94%, 75%, 71% and 67% removal of Pb, Zn, Cu and Cd could be achieved, respectively, on grinded tailings in 28 days. Sequential chemical extraction made before and after EDR revealed larger oxidisable fractions of Zn, Cu and Cd, representing large fractions of sulphides, which was likely to be the main barrier to be removed as efficiently as Pb. This was in accordance with acid/base extraction tests in which Pb showed high solubility at both high and low pH (up to 65% and 86% of extraction, respectively), while considerable extraction of Zn (55%) happened only at low pH; and very limited extraction (<20%) of Cu and Cd occurred at any pH.